(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
The hospitality industry is continuously evolving, driven by the need to enhance customer experience and satisfaction. Artificial intelligence (AI) has emerged as a transformative technology that can significantly elevate service standards in this sector. This research paper explores the multifaceted applications of AI in the hospitality industry, focusing on its potential to revolutionize customer service, personalize guest experiences, and optimize operational efficiency. Key AI technologies discussed include machine learning algorithms, chatbots, voice assistants, predictive analytics, and IoT-enabled smart rooms. Through personalized recommendations, automated customer service, and data-driven insights, AI enables hotels to anticipate and meet guest needs more effectively. The implementation challenges—such as data protection issues, integrating with current systems, and requiring staff training—are also covered in the article. The hospitality sector may increase operational efficiency and profitability while also improving visitor pleasure and loyalty by utilizing AI. This research attempts to give a thorough grasp of AI’s effects on hospitality and provide tactical advice for their effective use.